ENGINEERING AND TECHNOLOGY IN INDUSTRIAL CIVILIZATION CULTURE - Evgeny I. Sedov; Artur E. Sedov (Advanced Engineering Research)
Both internal logic of the engineering and technolo gy development, and their sociocultural aspect is analyzed. The concepts under study are considered in connection with the existence, activity, values of the society. Innovative information technology and engineering proliferation leads to the awareness th at considering numerous social fa ctors is no less imp ortant than the technical ones.